Evaluation of 902 Total Abdominal Hysterectomies Performed for Benign Reasons - Boynukalın, Fazilet Kübra; Güler, Ömer Tolga; Coşkun, Mehmet; Özyüncü, Özgür; Doğan, Nasuh Utku (Gynecology Obstetrics & Reproductive Medicine, 2014)
OBJECTIVE: Hysterectomy is the most frequently performed major surgery and is the most common major abdominal operation following cesarean section. The most common indication is uterine leiomyoma. The objective of this study is to evaluate the abdominal hysterectomy indications, intraoperative and postoperative complications and surgical morbidity. STUDY DESIGN: Demographic information, surgical indications, intraoperative and postoperative complications, hospitalization periods and clinical follow-up information of the patients who underwent abdominal hysterectomy at Hacettepe University Hospital, Department of Obstetrics and Gynecology between 2000 and 2004 were retrieved from patients’ files and follow-up forms. Statistical evaluations were performed using SPSS 10.0 for Windows program and p<0.05 values were considered as statistically significant. RESULTS: Among 902 patients in whom abdominal hysterectomy was performed the mean age was 47.9 (range: 30-77), and the most common hysterectomy indication was uterine leiomyoma (n=552, 61.2%). While abdominal hysterectomy alone was performed in only 87 patients (9.6%), bilateral salphingo-oophorectomy was added in 746 patients (82.7%) and unilateral salphingo-oophorectomy was performed in 69 patients (7.7%) together with hysterectomy. Among patients in whom bilateral salphingooophorectomy was performed, 569 (76.3%) were in pre-menopausal period. In 119 patients (13.2%) an additional surgical intervention was applied during operation. Burch procedure and appendectomy were performed in 5.5% and 3.8% of patients, respectively. Mean operation time was 1.21 hours and mean hospitalization period was 6.28 days. Intraoperative complication rate was 0.6% and visceral organ injury was the most commonly seen complication. Postoperative complications were seen in 17.1% of the patients and the most frequent postoperative complications were febrile morbidity and wound infection (10.1% and 4.3%, respectively). Preoperative and postoperative mean hemoglobin values were 11.9 and 10.3 gr/dL, respectively, and 7.5% of the patients received erythrocyte transfusion postoperatively. No operation related deaths were observed during the study period. CONCLUSION: Abdominal hysterectomy, the most frequently performed operation of gynecology clinics, is an effective treatment modality in relieving symptoms and increasing quality of life with relatively lower complication rates. However, its morbidity and complications is agreed to be higher when compared with those of vaginal hysterectomy. Therefore, vaginal approach should always be preferred if possible. When abdominal route is mandatory, an appropriate antibiotic prophylaxis should be used to decrease the rate of febrile morbidity which is the most commonly seen postoperative complication.